Combination of Storytelling and Music Therapy to Reduce Stress in Children with HIV/AIDS and Discrimination in Surabaya - Taufan Citra Darmawan (Jurnal Ilmiah Kesehatan, 2021)
Human Immunodeficiency Virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS) in Indonesia are deadly infectious diseases. This disease will always be a problem at the national and global levels. The impact that often occurs, especially in children with HIV/AIDS, is psychological changes, namely stress. Efforts to overcome its disturbance are storytelling and music therapy. This research aims to apply storytelling and music therapy to reduce stress in children with HIV/AIDS.    This research method was a quasi-experiment with a research design involving 1 group (one group pre-post test), containing 30 respondents aged 6-10 years with HIV/AIDS by purposive sampling. The independent variable was storytelling and music therapy, while the dependent variable was stress levels. The instrument used Hamilton Anxiety Questionaire (HAM-A). The results of the study showed that 26 samples (86.7%) experienced decreased stress levels. Analysis of  Wilcoxon sign rank test obtained α=0.009, which means there was a difference before and after therapy.    The combination of music therapy and storytelling can be a better alternative in reducing stress in children – by considering age, environment, and children's emotions to have an optimal effect.